2013
DOI: 10.1111/apt.12255
|View full text |Cite
|
Sign up to set email alerts
|

Phase II clinical trial of phlebotomy for non‐alcoholic fatty liver disease

Abstract: SUMMARYBackground Elevated iron indices are described in non-alcoholic fatty liver disease and iron reduction has been suggested as a potential therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(84 citation statements)
references
References 45 publications
6
76
2
Order By: Relevance
“…This is also supported by the indistinguishable responses of single Hjv -/-and double Hfe -/-Hjv -/-mice to dietary iron loading 2 and is in line with recent biochemical data suggesting that HFE stimulates hepcidin expression by stabilizing ALK3, a type I bone morphogenetic protein receptor. 3 It is known that HJV functions as a bone morphogenetic protein coreceptor that enhances the bone morphogenetic protein signaling pathway.…”
Section: Iron Regulation Of Hepcidin Through Hfe and Hjv: Common Or Dsupporting
confidence: 89%
See 2 more Smart Citations
“…This is also supported by the indistinguishable responses of single Hjv -/-and double Hfe -/-Hjv -/-mice to dietary iron loading 2 and is in line with recent biochemical data suggesting that HFE stimulates hepcidin expression by stabilizing ALK3, a type I bone morphogenetic protein receptor. 3 It is known that HJV functions as a bone morphogenetic protein coreceptor that enhances the bone morphogenetic protein signaling pathway.…”
Section: Iron Regulation Of Hepcidin Through Hfe and Hjv: Common Or Dsupporting
confidence: 89%
“…For example, the study referenced by Ryan et al as being controlled was actually a single-arm study. 2 Our prospective, multicenter, randomized, controlled trial, being the largest study of this type, was unable to detect any effect of iron reduction on liver steatosis, serum markers of liver injury, lipid peroxidation, insulin resistance, or quality-of-health measures.…”
Section: Replymentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast to hemoch romatosis patients, NAFLD subjects have impaired iron mobilisation from storage sites and may there fore develop anemia in response to phlebotomy treatment. We therefore recommend close monitoring of serum ferritin, TfS and hemoglobin at each visit for the period of time while these patients are on phlebotomy treatment [26,153] .…”
Section: What Is the Therapeutic Potential Of Modulating Iron Stores mentioning
confidence: 99%
“…Fujita et al [26] showed that iron reduction resulting from a-combination of phlebotomy and a low iron diet resulted not only in improvement of ALT levels but also normalization of hepatic levels of 8-OHdG in 11 NASH patients. In a phase Ⅱ trial on 31 patients with NAFLD, phlebotomy resulted in a significant improvement in the NAFLD activity score (NAS), AST and ALT [27] . In a phase Ⅲ trial, Valenti et al [28] studied 38 NAFLD patients randomized to phlebotomy (n = 21) or [16] 2007 Open labeled 35/40 Chronic hepatitis C…”
Section: Iron Depletion Therapymentioning
confidence: 99%